The Perfect Balance: Algorithmic Efficiency vs. Procedural Guarantees in Peruvian Public Procurement - Freitas Cabanillas, Rodrigo Andrés (2025)
This article analyzes the benefits and challenges involved in implementing artificial intelligence (AI) in Peruvian public procurement, highlighting both its potential to enhance efficiency, traceability, and transparency, as well as the risks that arise in the absence of an adequate legal and technical framework. It examines the tension between algorithmic efficiency and procedural safeguards, particularly due process, administrative reasoning, and the right of defense. Based on a normative, functional, and comparative analysis with references to experiences in Estonia, France, Singapore, Portugal, and Ukrainethis study identifies valuable lessons for the Peruvian context. Finally, it proposes a hybrid model of automation that reconciles technological innovation with legal safeguards, ensuring that AI strengthens the rule of law rather than undermines it.